Optimal Reactive Power Planning Using FACTS Devices for Voltage Stability Enhancement in Power Transmission Systems - Rawan Abu Zeitawyeh; Ayman Faza (Energy Science & Engineering)
ABSTRACT The increased demand for electricity has forced power systems to operate near their stability limits. Optimal reactive power planning (ORPP) can enhance voltage stability and provide much‐needed support for grid operation. Flexible AC transmission system (FACTS) devices can provide the necessary reactive compensation in the form of series and shunt compensation devices, which, together with Distributed Generation (DG) units, can enhance voltage stability and prevent potentially catastrophic events such as voltage collapse or blackouts. In this study, the L‐index and the fast voltage stability index (FVSI) are used to evaluate voltage stability in the system. Objective functions are developed that incorporate the cost of the FACTS devices and the stability indices to provide a basis for optimizing system operation. Optimization was performed for the series and shunt compensations separately. Moreover, a multi‐objective optimization is also presented that incorporates both devices together. Results show that using both series and shunt compensation enhances voltage stability. Furthermore, combining both methods provides a significant improvement over their individual enhancements. Increasing the penetration of DG sources also provides significant improvement in system stability. The main findings conclude that both real and reactive power injections can improve system stability; however, careful considerations should be made when choosing the best location and sizing for the FACTS devices and the DG sources to maximize the benefits of their use on voltage stability.